Парафиларондес Крашенинникова (Рагаfilaroides krascheninnikovi sp. n.) — паразит легких кольчатой нерпы (Pusahispida krascheninnikovi Naumov et Smirnov) - Юрахно, М.В.; Скрябин, А.С. (Вестник зоологии, 1971)
New species of Nematoda — Parafilaroides krascheninnikovi sp. n. is described from
the lungs of Pusa hispida krascheninnikovi Naumove t Smirno v inhabiting the Bering
and Chukotsk seas. The new species differs from all the species of the given genus in
relation of the width of oesophagus and that of the anterior part of guts from all the
species, except for P. hydrurgae — in greater dimensions of females from P. decorus,
P. nanus, P. caspicus and P. arcticus — in greater and from P. gymnurus and P. hydrurgae — less dimensions of males and some of their organs. From all the species, except for P. arcticus, it also differs in the host and place of finding. P. krascheninnikovi is most close to P. gymnurus, but differs from it in body dimensions of males and females, presence of gubernaculum, another host and another distribution region.